The civil and religious marriage in the interpretation of Polish law in the years of 1945–1993 - Rakoczy, Tomasz (The Opole Studies in Administration and Law, 2017)
The institution of marriage is important for the both systems of law: state and church, as both of these two bodies must respect the truth about the institution of marriage. As the analysis of the problem shows, i.e. the possibility of contracting marriage in the religious form and in presence of other religious elements, the mentioned rule was not always respected by the Polish State. Religious elements were in fact significantly present in different jurisdictions of the partitioning states, which were in force on Poland’s territory under the rule of individual partitioning states. The possibility of the presence of religious elements in executing institution of marriage was taken into account in discussion that took place in Poland after the year 1918. All projects of acts of law were unfortunately rejected. The first act of law that was promulgated in 1945 presented a completely new, strange and even inimical to the Polish tradition, lay model of executing the institution of marriage. Its tightening followed rapidly after the promulgation of the next act of law, i.e. the Code of Family in the year of 1950. A change came about in the year 1998 through the Polish Concordat which came into force beginning with the year 1993. The possibility of contracting a civil marriage in the religious form was opened first for the Catholic Church. At the next stage, the same possibility was recognized in the case of ten other churches. As the analysis of the problem shows, contracting of a civil marriage in the religious form has always stayed under the control of the registry office. A clergyman is only an executor of the procedure.